OC-056 High Rate of Missed Visible Lesions in Patients Referred with Low Grade Dysplasia with Subsequent Upstaging of Pathology by EMR in Majority. (17th August 2016) - Koumoutsos, I; Wilson, P; DeMartino, S; Dunn, J
Abstract : Introduction: Endoscopic therapy for Barrett's oesophagus (BE) associated dysplasia or intramucosal cancer (IMC) has become the standard of care, and is recommended to occur in regional centres with high volume. Endoscopic mucosal resection (EMR) is often the first step as the majority of patients with high grade dysplasia (HGD) will have a visible lesion. This has been shown to upgrade HGD to more advanced pathology in over 30%. Little data exists on the use of EMR for low grade dysplasia (LGD). Aim of this study is to assess the rate of visible lesions in patients referred with LGD and outcomes of EMR. Methods: Prospective study of patients undergoing BE dysplasia assessment at tertiary referral upper GI centre (GSTT). Surveillance endoscopy was performed with virtual chromoendoscopy (NBI) and conventional chromoendoscopy (acetic acid 2.5%) by two endoscopists, and EMR was undertaken, when feasible, to a visible lesion. Analysis was by independent t-tests for continuous variables and chi-squared tests for categorical variables. Results: A total of 69 patients with BE underwent endoscopy, between 2014 and 2016. Results are shown in table 1. Patients were split into community pathology referral grade. There was no significant difference in patient's age, sex or length of BE between the groups. EMR was undertaken to visible lesions in 84% of patients with HGD vs 54% with LGD. EMR was not performed due to advanced endoscopic lesions in 18% of patients referred with IMC, 13% with HGD and 4% for LGD. Pathology upstaging compared to the stage of the referring hospital was significantly higher in EMR specimens (50%) vs central pathology review of biopsies (19%) (p-value:0.001). There was no statistical difference in the rates of patients upstaged from EMR from patients referred with LGD vs HGD (64% vs 54%, p-value:0.75). In 3/26 (11%) of patients referred with LGD pathology of EMR specimen showed IMC. Conclusion: This study demonstrates a high rate of missed visible lesions in patients diagnosed with LGD in a community setting, with half undergoing EMR. That these patients were upstaged to higher grades of dysplasia in 64% of the cases, indicates correct choice of EMR as a diagnostic modality in this group. Endoscopists carrying out surveillance endoscopy for patients with LGD should be aware of a high rate of visible lesions and advanced pathology, and consider referral to centre for further endoscopic evaluation. Disclosure of Interest: None Declared